Thinking Like a Lawyer: The Case for Roman Law - du Plessis, Paul (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of this piece is to present an overview of certain recent trends which have emerged in the study and teaching of Roman law. These trends are identified and placed within the larger context of the role and function of the teaching of Roman law in Law Schools during the twentieth century. In addition, it is argued in this piece that trends regarding the study of Roman legal sources which have emerged in the context of U.S. Law Schools have the potential to enrich the discipline and to permit new questions to be asked about Roman law.